2019
DOI: 10.1155/2019/4586265
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis and Multiple Myeloma: A Case Report and Literature Review

Abstract: The existence of a sarcoidosis-lymphoma syndrome has been previously proposed since the relation between sarcoidosis and an increased risk of lymphoproliferative disorders is well established. Multiple myeloma is a malignant multifocal proliferation of clonal plasma cells within the bone marrow, and its association with sarcoidosis has been rarely described. We present a concurrent diagnosis of sarcoidosis and multiple myeloma and make a brief analysis of the reported cases in the literature. A 65-year-old wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
(17 reference statements)
1
5
0
Order By: Relevance
“…Osseous lesions were found in the spine and were accompanied by ocular and nodular involvement. Similar cases are summarized by Tiago Serra et al [49]. Association of sarcoidosis with lymphoma has been sporadically reported as well.…”
Section: Detection Of Osseous Involvement In Patients With Sarcoidosissupporting
confidence: 71%
“…Osseous lesions were found in the spine and were accompanied by ocular and nodular involvement. Similar cases are summarized by Tiago Serra et al [49]. Association of sarcoidosis with lymphoma has been sporadically reported as well.…”
Section: Detection Of Osseous Involvement In Patients With Sarcoidosissupporting
confidence: 71%
“…There are a number of possible explanations for these associations, including immune system dysregulation with activation of CD4+T-helper/inducer cells, increased secretion of various cytokines and decreased CD8+T-suppressor/cytotoxic cells 14. On review of the previous cases of sarcoidosis in association with multiple myeloma reported in the literature, the median age at diagnosis of the sarcoidosis is older than that reported for cases of sarcoidosis diagnosed in the general population 9. There is also a female predominance among the reported of sarcoidosis in association with multiple myeloma 9.…”
Section: Discussionmentioning
confidence: 86%
“…The association between sarcoidosis and lymphoma is well established and the sarcoidosis-lymphoma syndrome was first described in 1986 by Brincker and Wilbek 8. However, there are very few reports of an association between sarcoidosis and multiple myeloma 9–12. Herein, we report a case of paraneoplastic sarcoidosis occurring in a patient progressing from smouldering to symptomatic multiple myeloma.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Some patients with sarcoidosis and myeloma may present AKI, associated with hypergammaglobulinemia, normal albuminemia and hypercalcemia. In these cases, the differential diagnosis between sarcoidosis and multiple myeloma may be difficult ( 44 , 45 ). Bone marrow biopsy, showing non-caseating granulomas or prompt improvement of hypercalcemia and kidney function after corticosteroid administration may lead to a correct diagnosis ( 46 ).…”
Section: Methodsmentioning
confidence: 99%